A new record of species Rubia tinctorum L. (Rubiaceae) for the flora of Vietnam - Tai, Vu Anh (Academia Journal of Biology, 2013)
In this paper, one species that was collected at high elevation of Fansipan Mountain (higher 2000 m a.s.l.) was identified as Rubia tinctorum L.. This species is new record for the flora of Vietnam. This species is also recorded as a medicine and also dyeing one. The specimens of this species were kept at the herbarium of Vietnam National University, Hanoi (HNU) and the herbarium of Hoang Lien National Park. Key to species of genera Rubia and Galium (3 species in Vietnam) of family Rubiaceae in Vietnam is provided. R. tinctorum differs from R. cordifolia by having non petiole and 4-6 whorled leaves (R. cordifolia is always 4 whorled leaves and petiole is 4-8 mm).